The Effect Of Frankel 3 Applıance On Nasal Resıstance" (A Cephalometrıc-Planımetrıc Study) - Enis Güray; Hasan Ayral; Şeyda Ersoy (Galenos Yayinevi, 1993)
In our study, the effect of Frankel 3 appliance on nasal resistance was evaluated in Angle Class 3 cases. For the study, 7 females and 13 males, total 20 individuals were treated as treatment group as well as 7 females and 7 males total 14 individuals were members of control group. The planimetric measurements were done on the lateral cephalometric radiograms taken before and after the treatment. As a result of this study, a decreased nasal resistance was found by using "Mann Whitney U" test, in the individuals which were treated with Frankel 3 appliance. And also by using "Student t" test, it was observed that the location of the tongue and the mandible had not gained any change.